Scenario of carbon dioxide (CO2) emission peaking and reduction path implication in five northwestern provinces of China by the low emissions analysis platform (LEAP) model - Zhang, Zhenxu; Jia, Junsong; Guo, Yali; Wu, Bo; Chen, Chundi (Frontiers in Energy Research, 2022)
Achieving global peaking of carbon dioxide (CO2) emissions as early as possible is a common goal for all countries. However, CO2 emissions in the northwest China still show a rapid growth trend. Thus, we used the Low Emissions Analysis Platform (LEAP) model to build three scenarios to investigate the peak of CO2 emissions and reduction pathways in five northwestern provinces of China. The results show that: 1) the CO2 emissions of five northwestern provinces under the baseline, the policy, and the green scenarios will peak in 2035 (1663.46 × 106 tonnes), 2031 (1405.00 × 106 tonnes), and 2027 (1273.96 × 106 tonnes), respectively. 2) The CO2 emissions of all provinces, except Qinghai, will not peak before 2030 in the baseline scenario. Under the policy and green scenarios, each province will achieve the peak of CO2 emissions by 2030. 3) The CO2 emissions from agriculture, transportation, and other sectors will peak before 2030 under the baseline scenario. The CO2 emissions from construction will peak before 2030 in policy scenario. The industry and commerce will peak before 2030 in green scenario. 4) The emission reduction effect indicates that CO2 emissions from 2020 to 2040 will be reduced by 4137.70 × 106 tonnes in the policy scenario and 7201.46 × 106 tonnes in the green scenario. The industrial coal and thermal power are the sectors with the greatest potential to reduce CO2 emissions. Accelerating the restructuring of industries and energy structures and improving technologies to reduce energy intensity can promote the achievement of the peak in CO2 emissions by 2030.